A Note on some Characterization of Distributive Lattices of Finite Length - Łazarz, Marcin; Siemieńczuk, Krzysztof (Bulletin of the Section of Logic, 2015)
Using known facts we give a simple characterization of the distributivity of lattices of finite length.